Spontaneous enhancement of the stable power conversion efficiency in perovskite solar cells. Issue 2 (12th December 2019) - Moghadamzadeh, Somayeh; Hossain, Ihteaz M.; Jakoby, Marius; Abdollahi Nejand, Bahram; Rueda-Delgado, Diana; Schwenzer, Jonas A.; Gharibzadeh, Saba; Abzieher, Tobias; Khan, Motiur Rahman; Haghighirad, Amir A.; Howard, Ian A.; Richards, Bryce S.; et al.
Abstract : This work studies spontaneous enhancement in power conversion efficiency of multi-cation-halide perovskite solar cells which occurs days after device fabrication. Abstract : The power conversion efficiency (PCE) of lead-halide perovskite solar cells (PSCs) is reported to increase over a period of days after their fabrication while they are stored in the dark. The effects underlying this spontaneous enhancement thus far are not understood. This work investigates the phenomenon for a variety of multi-cation-halide PSCs with different perovskite compositions and architectures. The observations reveal that spontaneous enhancement is not restricted to specific charge transport layers or perovskite compositions. The highest PCE observed in this study is an enhanced stable PCE of 19% (increased by 4% absolute). An increased open-circuit voltage is the primary contributor to the improved efficiency. Using time-resolved photoluminescence measurements, the initially present low-energy states are identified which disappear over a storage period of a few days. Furthermore, trap states probed by the thermally stimulated current technique exist in pristine PSCs and strikingly decrease for stored devices. In addition, the ideality factor approaches unity and X-ray diffraction analyses show lattice strain relaxation over the same period of time. These observations indicate that spontaneous enhancement of the PCE of PSCs is based on a reduction in trap-assisted non-radiative recombination possibly due to strain relaxation. Considering the demonstrated generality of spontaneous enhancement for different compositions of multi-cation-halide PSCs, our results highlight the importance of determining the absolute PCE increase initiated by spontaneous enhancement for developing high-efficiency PSCs.